Some aspects of Bay of Bengal Cyclone of October 1963 - ANJANEYULU, T. S. S.; SIKKA, D. R.; GURUNADHAM, G. (MAUSAM, 1965)
An attempt has been made to study the structure of the circulation through the entire troposphere around the cyclonic storm which formed in the Bay of Bengal and crossed Coromandal Coast near Cuddalore and lay near Vellore on 21 October 1963 (1200 GMT).. Latent heat and sensible heat energy have been estimated around the lateral boundary of the storm circulation and heat and moisture fluxes computed. The circumstances under which the system recurved and the cause for the heavy precipitation far away from the storm centre have also been briefly discussed.